IODIDE-ION QUENCHING OF THE PHOTOLYSIS OF 1-IODOANTHRAQUINONE ANION RADICAL - EVIDENCE FOR AN ARYL RADICAL NUCLEOPHILE REACTION - Bethell, D; Compton, R; Wellington, R (1992)
The photolysis of 1-iodoanthraquinone anion radical in acetonitrile containing tetrabutylammonium iodide(TBA+l-) is unaffected by changes in [TBA+|-] up to 0.2 mol dm-3, confirming that the previously observed iodide ion quenching results from capture of photogenerated aryl radicals by the nucleophilic iodide, a process analogous to that in nucleophilic aromatic substitution by the SRN1 mechanism.